IDENTIFIKASI ENUMERATION STRATEGY (ENGLISH) SISWA HASIL IMPLEMENTASI STUDENT WORKSHEET BERBASIS PENALARAN KOMBINATORIK DI SEKOLAH DASAR - Nurul Aini; Eny Suryowati (Prosiding Conference on Research and Community Services, 2023)
Enumeration Strategy is part of the combinatoric reasoning strategy. Experts argue that by knowing the enumeration strategy used, one can find out about the systematic way of reasoning. This can affect in solving problems. However, this enumeration strategy is often overlooked. Thus, the aim of the research is to identify students' enumeration strategies resulting from the implementation of student worksheets based on combinatorial reasoning in elementary schools. This type of research is descriptive qualitative, the research subjects consisted of 40 students of class VI MI Muhammadiyah 1 Jombang. The instruments used are student worksheets and interview guidelines. The analysis refers to English theory. The results showed that 50% of students used trail and error, 37,5% used the odometer complete and 12.5% used the odometer with error. So the Enumeration Strategy that appears is trail and error, odometer with error and odometer complete